ORIENTALISTS AND THEIR STUDY OF THE QUR’AN - Nazar Fadli; Triansyah Fisa; Muhammad Faisal (Teunuleh Publisher, 2020)
The study of orientalists and their thoughts on the eastern world became one of the important studies for Muslim scholars. Especially his thoughts concerning the most substantial things in the eastern world. The eastern world that is synonymous with Islam is very interesting to be studied by Western Scholars. The Qur'an which became the main source of life for Muslims became the most important object studied by orientalists. Generally orientalists opinions of the Qur'an give birth to negative opinions that tend to criticize the authenticity of the Qur'an. Orientalists approache in the study of the Qur'an can be grouped into three parts. The first, Historically-critical, that is, reviewing a narrative by looking at what really happened. These criticisms include forms, editors, and sources. The second. Interpretive interpretation, i.e. interpreting the text using one of three methods; philology, literature, and linguistics. The third, phenomenologists, namely describing the reception of the Qur'an carried out by individuals of a particular group. According to Syamsuddin Arif, there are many ways or techniques used by orientalists to question their authenticity, where the classic issue that is often raised is the influence of Jews, Christians, Zoorosters, and so on Islam and cages in the Qur'an (Theories of borrowing and influence). Some of them are trying to reveal what could be evidence for the loan theory and its influence. Especially from Jewish-Christian literature and traditions (such as Abraham Geiger, Clair Tisdall, and others). There are also those who compare the teachings of the Qur'an with the customs of Jahiliyyah, Roman, and so on.